Involvement of the flagellar assembly pathway in Vibrio alginolyticus adhesion under environmental stresses - Wang, Lu; Huang, Lixing; Su, Yongquan; Qin, Yingxue; Kong, Wendi; Ma, Ying; Xu, Xiaojin; Lin, Mao; Yan, Qingpi (Frontiers in Cellular and Infection Microbiology, 2015)
Adhesion is an important virulence factor of Vibrio alginolyticus. This factor may be affected by environment conditions; however, its molecular mechanism remains unclear. In our previous research, adhesion tender models were obtained by culturing V. alginolyticus under stresses such as Cu2+, Pb2+, Hg2+, and low pH. With high-throughput sequencing and bioinformatics analysis, we found that all of these stress treatments significantly affected the flagellar assembly pathway, which may play an important role in V. alginolyticus adhesion. Therefore, we hypothesized that the environmental stresses of the flagellar assembly pathway may be one way in which environment conditions affect adhesion. To verify our hypothesis, a bioinformatics analysis, QPCR, RNAi, in vitro adhesion assay and motility assay were performed. Our results indicated that 1) the flagellar assembly pathway was sensitive to environmental stresses, 2) the flagellar assembly pathway played an important role in V. alginolyticus adhesion, and 3) motility is not the only way in which the flagellar assembly pathway affects adhesion.